Letter from Max Bredig to Georg Bredig and Marianne Homburger, August 9, 1936 - Bredig, Max Albert (1936)
Max Albert Bredig (1902-1977) describes a job opportunity in the United States and his visit to the Olympic Stadium in 1936 to his father, Georg Bredig (1868-1944) and sister, Marianne Homburger (1903-1986).
Keywords: Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Olympics; Job hunting